Synthesis of Anti-Inflammatory Drugs’ Chalcone Derivatives and a Study of Their Conformational Properties Through a Combination of Nuclear Magnetic Resonance Spectroscopy and Molecular Modeling - Nikitas Georgiou; Andromachi Tzani; Kyriaki Vavougyiou; Christos Papadopoulos; Nikolaos Eleftheriadis; Primož Šket; Demeter Tzeli; Tuomas Niemi-Aro; Anastasia Detsi; Thomas Mavromoustakos (Pharmaceuticals)
Background: In this study, two chalcone analogs were synthesized through in silico and experimental methods, and their potential to inhibit the lipoxygenase enzyme, which plays a role in the inflammation pathway, was assessed. Specifically, this study is a continuation of previous research in which chalcone derivatives were synthesized and characterized. Objectives/Methods: In the current work, we present the re-synthesis of two chalcones, with a focus on their docking studies, NMR analysis, and dynamic simulations. The structure of each chalcone was elucidated through a combination of Nuclear Magnetic Resonance (NMR) and Density Functional Theory (DFT). The substituent effect on the absorption spectrum of the two chalcone derivatives was studied. Results: A “LOX–chalcone” complex, predicted by docking studies, was further examined using molecular dynamics (MD) simulations to evaluate the stability of the complex. After fully characterizing the “LOX–chalcone” complexes in silico, the atomic details of each chalcone’s interaction with LOX-1 and 5-LOX were revealed through Saturation Transfer Difference (STD) NMR (Nuclear Magnetic Resonance). Finally, their selectivity profile was investigated against human 15-LOX-1 and general Lipoxidase activity. Conclusions: The in silico methods suggest that chalcones could be promising lead compounds for drug designs targeting the LOX enzyme.